'Leh wi tok for change wi village' : Community Dissemination of Research Findings - Jalloh, Gibrill S (World Bank, Washington, DC, 2018)
Drama has long been used to promote community dialogue on social and political change. The recent experience of the World Bank's Justice for the Poor (J4P) program in Sierra Leone shows that drama can be a particularly effective medium for engaging poor and illiterate communities. J4P, in partnership with the Campaign for Good Governance (CGG), a local Non Governmental Organization (NGO), recently teamed with a community drama group, Future Leaders Action Group for Education (FLAGE), to disseminate the findings of J4P's research on local level governance and justice administration in Sierra Leone. The dissemination program provided an opportunity to thank those communities that hosted researchers during the field research, and to encourage community ownership of the research findings. J4P's experience shows that drama can help to create a space for dialogue between authorities and vulnerable groups. In a context where many community members are illiterate, drama can also raise awareness of ongoing disputes and encourage community members to identify possible solutions.